2016
DOI: 10.5539/gjhs.v8n9p159
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Blood Glucose and Electrolytes during Cardiopulmonary Bypass in Diabetic and Non-Diabetic Patients of Pakistan

Abstract: Introduction:Perioperative hyperglycemia has been shown to be related to higher levels of morbidity and mortality in patients on cardiopulmonary bypass (CPB) undergoing coronary artery bypass grafting (CABG), both diabetic and non-diabetic. Blood electrolytes, like sodium, potassium, calcium, and chloride play a very important role in the normal functioning of the body and can lead to a variety of clinical disorders if they become deficient. A minimal number of studies have been conducted on the simultaneous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
1
1
1
Order By: Relevance
“…The lack of awareness among the participants in the current study is consistent with findings of previous Pakistani studies, which also reported inadequate awareness about the risk factors related to NCDs affecting patients' adherence to lifestyle modifications. 18,19 In contrast, studies in developed countries like China 20 and the USA 21 reported higher awareness and knowledge among patients who were living with hypertension, possibly attributable to differences in literacy rates of the population, as more than half of the participants in our study had no education which technically meant that they could not read and write their names. Despite widespread prevalence of hypertension, and its prediction to rise steeply, 22 previous and current studies have shown that low patient awareness about the hypertension, its risks, and complications is ubiquitous.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The lack of awareness among the participants in the current study is consistent with findings of previous Pakistani studies, which also reported inadequate awareness about the risk factors related to NCDs affecting patients' adherence to lifestyle modifications. 18,19 In contrast, studies in developed countries like China 20 and the USA 21 reported higher awareness and knowledge among patients who were living with hypertension, possibly attributable to differences in literacy rates of the population, as more than half of the participants in our study had no education which technically meant that they could not read and write their names. Despite widespread prevalence of hypertension, and its prediction to rise steeply, 22 previous and current studies have shown that low patient awareness about the hypertension, its risks, and complications is ubiquitous.…”
Section: Discussioncontrasting
confidence: 58%
“…Medication adherence was seen in 72% of the participants amongst all socio-economic strata. Higher level of medication adherence has also been reported by previous studies 19,27,30 conducted with cardiac patients where medication compliance was taken relatively seriously by the participants as compared to any other self-management behavior. Participants give importance to the prescription because they are personalized and directly written by the doctors whom they are answerable to on subsequent visits.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The hyperhydrated patient may present facial or generalized edema, ascites, pleural effusion, respiratory failure, asthenia, disorientation, delirium and seizures or other neurological manifestations. Hyperhydration is a complication that is accentuated in patients with low amounts of proteins in the body, representing another risk factor for this individual when performing surgical procedures, considering that the oncotic pressure of the plasma is reduced and allows extravasation of liquids from the plasma to the interstitial space, especially if the liquid supply is not adequately dimensioned [31,32].…”
Section: Metabolic Responsementioning
confidence: 99%
“…In this context, sodium (Na + ) is the main ion for sustaining water balance, since its loss can cause a reduction in extracellular osmotic pressure and, consequently, cause the transition from this compartment to the intercellular compartment. However, if there is an increase in extracellular sodium levels, there is an increase in osmotic pressure and, consequently, this results in the interstitial accumulation of water, with the development of edema [31,32].…”
Section: Metabolic Responsementioning
confidence: 99%